Systems-of-Systems Perspectives and Applications Design, Modeling, Simulation and Analysis (MS&A), Gaming and Decision Support - Nguyen, Tien M. (IntechOpen, 2021)
This professional technical book presents complex topics on System-of-System (SoS) and Systems-of-Systems (SOS) engineering, SOS enterprise architecture (SOSEA) design and analysis, and implementation of SOSEA framework along with the modeling, simulation and analysis (MS&A) models in MATLAB. In addition, the book also extends the use of SOS perspectives for the development of computer simulation models for complex processes, systems, decision support systems, and game-theoretic models. This book is intended for two reader categories; namely, a primary and secondary category. The primary category includes system engineers, SOS architects, and mathematicians. The secondary category includes scientists and researchers in space/airborne systems, wireless communications, medicine, and mathematics, who would benefit from several chapters that contain open problems and technical relevance.